Selecting Temporary Flood Shelter Locations by P-Center Model - Wichitsawat Suksawat Na Ayudhya (2021 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2021)
Eastern Special Development Zone (ESDZ) is the key project of Thai government to promote economy. However, a province located in ESDZ zone is prone to suffer from floods because of its geographic position. We study locations of temporary flood shelters. We formulate our problem by using P-Center model since want to select locations of temporary flood shelter so that they minimize the maximum distance from the flooded area (districts) to temporary shelters. We also incorporate the historical data of traveling distance affected by floods and the population of each district into our model. We test our model against real-life data under various scenarios. Our numerical experiment results show that Mueang Chachoengsao and Kabin Buri districts are the key locations for temporary flood shelters.
Keywords: Facility Location and Emergency Management; Evacuation and Crowd Dynamics; Transportation Planning and Optimization